Peran Bazar Umkm Sebagai Strategi Pemberdayaan Perempuan dalam Meningkatkan Ketahanan Ekonomi Keluarga di Desa Paya Angus: Penelitian - Dealfi Anggun Fratiwi; Cut Mutia Rani; Madiha Layanah; M. Faiz Javier; Fitryia Rahma Putri; Dini Febriyanti; Rofi’ul Amri; Imam Warmansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Family economic resilience in Paya Angus Village faces pressures from global dynamics, pandemic effects, and price fluctuations, with women playing a key role via MSMEs. This study aims to analyze the role of MSME bazaars as a women's empowerment strategy to enhance such resilience. Employing a descriptive qualitative approach, the population includes women MSME actors, village officials, and bazaar organizers; purposive sampling was used until data saturation. Instruments comprised participatory observation, semi-structured interviews, and documentation, analyzed via Miles and Huberman model involving data reduction, display, and verification with triangulation. Findings reveal bazaars boost sales income, self-confidence, and household economic diversification, despite capital and digital marketing constraints. The conclusion affirms bazaars as effective sustainable empowerment tools requiring training and market access support.